(untitled) (Revista Contexto & Educação, 2024)
This article presents, from a qualitative approach, the influence of the humanities and the understanding of the impacts of hermeneutic disciplines on legal education, based on perception, experience in the training trajectory and in teaching practice. The participants were chosen from the consultation of the Higher Education Institutions (HEI) website, constituting a corpus of six teachers, two from each HEI, one that teaches technical subjects and another humanistic. The interpretation of the responses to the questionnaire occurred through content analysis, in which the categories were interpreted: 1) Influence of humanistic disciplines on legal training; 2) Participation of humanistic disciplines in the curriculum of courses; 3) Student receptivity of humanistic disciplines. It was found that humanistic disciplines, in particular, those of a hermeneutic character, in addition to being a counterpoint to normative positivism, it envisions the possibility of critical-reflexive legal teaching, which promotes the conditions for understanding Law and the world of life.